PENINGKATAN PEMBELAJARAN SEPAK BOLA DENGAN PERMAINAN DOUBLE SOCCER PADA SISWA KELAS V SEKOLAH DASAR NEGERI UJUNGWATU (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2014)
The purpose of this study was to look for the trouble-shooting practically orienting at action. Where each;every sikuls consisted by 4 phase that is (1) planning phase, (2) action Phase, (3) observation Phase, (4) phase refleksi to form of game of football of double soccer to student of class of V of Elementary School of Country 01 Ujungwatu. Research metode used by is (1) method of enquette of study expert, (2) enquette method of student. this Subyek Research that is entire/all student of class of V SD of Country Ujungwatu 01 a number of 21 consisted of by 13 student man and 8 girls. Technics analyse the data used by is descriptive of presentase to express the aspect psikomotorik, cognate, and avectyv student. Result of research, at cycle of I of data acquirement evaluate the assessment from expert obtained by result 58,00 % (enough), cycle of II obtained by result 86,00 % ( good), while [at] Cycle I of is percentage of answer of kuesioner student of equal to 54,00 % (enough), and Cycle II of is percentage of answer of cuesioner student of equal to 89,00 % (good). From inferential research result that football study (pass/through) the game of this football double soccer can be used to student of class of V SD of Country Ujungwatu 01 District of Donorojo of Sub-Province Jepara with the good result.